Knowledge, attitudes, and practices of human papillomavirus and self-sampling among adult women: a cross-sectional study - Shao, Juan; Ke, Huihui; Jiang, Cui; Sun, Huanmei; Han, Hongyu; Zhu, Jianlong; Chen, Li; Wang, Yingchen; Gu, Jiashi; Duan, Yingchun (Frontiers in Public Health, 2024)
Background This study aimed to investigate the knowledge, attitude, and practice (KAP) of human papillomavirus (HPV) and self-sampling among adult women. Methods The cross-sectional, questionnaire-based study included adult women at Shanghai Pudong Hospital from October 14, 2022, to March 31, 2023. The questionnaire contained demographic information, knowledge, attitude and practice dimensions. Factors associated with KAP and self-sampling were identified by multivariate logistic regression. Results A total of 1843 valid questionnaires were collected. The average knowledge, attitude, and practice score was 10.09 ± 5.60, 26.76 ± 3.80, and 6.24 ± 2.20, respectively. Urban residents (estimate = 0.705, p < 0.001), suburban residents (estimate = 0.512, p < 0.001), as well as individuals with undergraduate degrees and higher (estimate = 0.535, p < 0.001), were associated with good knowledge, while individuals lacking a history of HPV infection (estimate = −0.461, p < 0.001) and married individuals (estimate = −0.185, p < 0.001) were less likely to have good knowledge. Higher knowledge scores (estimate = 0.087, p < 0.001) and individuals with undergraduate education and above (estimate = 1.570, p < 0.001) were associated with a positive attitude. Being married (estimate = 0.291, p = 0.049) was associated with good practice, whereas not engaging in sexual activity (estimate = −0.959, p < 0.001) or lacking a history of HPV infection (estimate = −0.499, p = 0.011) were associated with unfavorable practices. Minorities (OR = 2.787, p = 0.038) and individuals with multiple sexual partners (OR = 2.297 for two partners, OR = 2.767 for three or more partners, p = 0.020 and p = 0.022) were positively associated with self-sampling. However, higher knowledge (OR = 0.952, p = 0.026) and attitude scores (OR = 0.929, p = 0.015) were negatively associated with self-sampling. Conclusion Demographic and behavioral factors significantly influenced KAP scores and self-sampling behaviors regarding HPV. Urban residency, higher education levels, positive attitudes, and minority status correlated with favorable outcomes, while factors like marriage and lack of sexual activity were associated with less favorable practices.